2022
DOI: 10.1177/13691481221075925
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the populist ‘mind’: Anxiety, fantasy, and everyday populism

Abstract: This article is focused on the appeal of far-right populist politics in the everyday and how this appeal is related to continuity and change in the global order. Contemporary societies have witnessed an upsurge of populist movements and groups set on filling a political space by appealing to a population in search of solutions to an ever-changing political and economic landscape. Here, we specifically highlight the role of ontological insecurity, fantasy narratives, and emotional governance as critical for und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 84 publications
0
16
0
1
Order By: Relevance
“…Elaborating on the psychology of anger vs. ressentiment invites the study of emotional mechanisms shaping the political outputs of grievance politics across Western and non-Western populist, nationalist, and authoritarian contexts (Kisić Merino et al, 2021;Sharafutdinova, 2020). The appeal of such rhetoric and narratives, particularly on the far-right, feeds and grows through subjective and intersubjective perceptions of threat and vulnerability (Kinnvall & Svensson, 2022;Salmela & von Scheve, 2017). Crucially, the outputs of grievance in ressentiment are not the outputs of grievance in anger.…”
Section: Discussionmentioning
confidence: 99%
“…Elaborating on the psychology of anger vs. ressentiment invites the study of emotional mechanisms shaping the political outputs of grievance politics across Western and non-Western populist, nationalist, and authoritarian contexts (Kisić Merino et al, 2021;Sharafutdinova, 2020). The appeal of such rhetoric and narratives, particularly on the far-right, feeds and grows through subjective and intersubjective perceptions of threat and vulnerability (Kinnvall & Svensson, 2022;Salmela & von Scheve, 2017). Crucially, the outputs of grievance in ressentiment are not the outputs of grievance in anger.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, scholars point to how ‘being’ is always incomplete and, in Lacanian (1988) terms, bound to narrative desires and fantasies (Browning, 2019; Eberle, 2019; Kinnvall & Svensson, 2022). As Kinnvall and Svensson (2022) argue, a focus on desire and fantasy narratives illuminates how the search for ontological security is a story – a fantasy – that can never be fulfilled. In responding to increased feelings of ontological insecurity, people, groups and state representatives thus temporarily close down categorical identifications.…”
Section: Normalisation Fantasy Emotional Governance and Ontological (...mentioning
confidence: 99%
“…Such rules are employed via official rituals and discursive practices (see also Hutchison and Bleiker, 2014; Holland and Solomon, 2014). A particular focus of this literature has been on crisis and trauma as emotional contexts in which ‘sites of affective investment’ arise, manifest in governments’ responses to, for instance, September 11 (Solomon, 2012) or the Covid-19 pandemic (Kinnvall & Svensson, 2022). In more general terms, Richards (2013) has suggested that all leaders, politicians and movements are engaged in reading and responding to feelings that are out there, and how they by these very acts are engaged in emotional governance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations